The “little man” in Tatyana Tolstayas prose - Golikova, Guzel; Khairova, Irina (Przegląd Wschodnioeuropejski, 2017)
The aim of the article is to reveal peculiarities of implementation of the theme and the image of the “little” person in the stories by Tatyana Tolstaya, show artistic form of interaction with Gogol and Gogol’s images according to the particular aesthetics of the writer. Playing with Gogol’s characters – Bashmachkin, old-world landowners, using Gogol’s chronotope, the composition, the writer translates the classic theme in ironic-parody plan. Neo-romantic orientation of Tolstaya’s texts leads to the existence of a particular philosophical component. Postmodern dominant determines the game with “word”: citations, intertextuality. Special aesthetic game with the classics allows the writer to convey the nature of the modern era, the cynicism and absurdity.